2018
DOI: 10.24326/asphc.2018.6.15
|View full text |Cite
|
Sign up to set email alerts
|

CHANGES IN CHLOROPHYLL a FLUORESCENCE AND PIGMENTS COMPOSITION IN OAK LEAVES WITH GALLS OF TWO CYNIPID SPECIES (Hymenoptera, Cynipidae)

Abstract: Gall-inducing insects may cause multiple physiological changes in host plants, such as the loss of photosynthetic pigments and reduced photosynthetic capacity. However, the direction of these changes is usually insect species-dependent. Therefore, the objective of this research was to characterize the indirect effects of galls induced by asexual generation of Neuroterus numismalis (Fourc.) and N. quercusbaccarum L. on photosynthesis by comparing changes in photosynthetic and photoprotective pigments and chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…According to Dorchin et al (2006), gall-inducing species that feed on specialized nutritive tissues (e.g., cynipid wasps) cause less damage to surrounding tissues, thus it is more likely that assimilation rates will increase. However, other findings (Aldea et al, 2006;Kot et al, 2018b) and the results presented here showed no evidence to support this hypothesis. Galling process of N. quercusbaccarum on oaks leaves caused a decrease of the maximum quantum yield of photosystem II (F v /F m ), which characterizes the functional state of PSII in dark-adapted leaves.…”
Section: Controlcontrasting
confidence: 94%
See 2 more Smart Citations
“…According to Dorchin et al (2006), gall-inducing species that feed on specialized nutritive tissues (e.g., cynipid wasps) cause less damage to surrounding tissues, thus it is more likely that assimilation rates will increase. However, other findings (Aldea et al, 2006;Kot et al, 2018b) and the results presented here showed no evidence to support this hypothesis. Galling process of N. quercusbaccarum on oaks leaves caused a decrease of the maximum quantum yield of photosystem II (F v /F m ), which characterizes the functional state of PSII in dark-adapted leaves.…”
Section: Controlcontrasting
confidence: 94%
“…Therefore, all fluorescence parameters mentioned above should also be analyzed (Huang et al ., 2013). In this study, a significant decrease of F m and F 0 values was observed, which proved, together with our previous study (Kot et al ., 2018 b ), that Cynipidae species that induce galls on leaves exerted a negative effect on photosynthetic rates. The occurrence of N. quercusbaccarum galls also resulted in a strong down-regulation of the effective quantum yield of photosystem II photochemistry ( Y ), i.e., the measure of the actual photochemical efficiency of PSII in illuminated leaves (Vassilev & Manolov, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that fatty acids are converted into sugars to feed the growing larva (Martinson et al, 2022). Finally, cynipid galls have previously been shown to contain lower concentrations of chlorophyll and carotenoids (Kot et al, 2018b;Kot et al, 2020), suggesting reduced photosynthesis as an explanation for the reduction in apocarotenoids observed here.…”
Section: Metabolomic Profiles Of Different Gall Types Are Distinct An...mentioning
confidence: 51%
“…The galls attached to leaves have a broader impact on the leaf to which it is attached. Leaves with galls exhibit reduced photosynthesis, chlorophyll, and carotenoid levels (Kot et al, 2018b, Kot et al, 2020). Additionally, there are increases in free radicals and defensive responses (Kot et al, 2018a, Kot and Rubinowska, 2018, Kot et al, 2019).…”
Section: Introductionmentioning
confidence: 99%